2013
DOI: 10.1093/europace/eus440
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of remote monitoring of CIEDs in detection and treatment of clinical and device-related cardiovascular events in daily practice: the HomeGuide Registry

Abstract: AimsThe HomeGuide Registry was a prospective study (NCT01459874), implementing a model for remote monitoring of cardiac implantable electronic devices (CIEDs) in daily clinical practice, to estimate effectiveness in major cardiovascular event detection and management.Methods and resultsThe workflow for remote monitoring [Biotronik Home Monitoring (HM)] was based on primary nursing: each patient was assigned to an expert nurse for management and to a responsible physician for medical decisions. In-person visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 18 publications
(20 reference statements)
4
118
0
5
Order By: Relevance
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Пожалуй, наиболее позитивный факт об этих устройствах состоит в том, что они предостав-ляют достаточно точную информацию о частоте, дли-тельности эпизодов ФП и общем времени, в течение которого у пациента была ФП (особенно касается аппаратов длительного подкожного мониторинга ЭКГ) [8]. Botto, et al показали, что частота инсульта у пациентов с кардиостимулятором и анамнезом ФП не зависит только от прогностических шкал, таких как шкала CHADS 2 , но также от реальной частоты, продолжительности и времени, в течение которого пациент находится в состоянии ФП, что можно уви-деть при опросе этих устройств.…”
Section: сложности в определении групп риска больных с фпunclassified
“…During a mean follow-up of 16±7 and median of 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months, 562 patients were enrolled. The baseline characteristics of the study population are shown in Table 1.…”
Section: Study Populationmentioning
confidence: 99%
“…15 The shift from ambulatory visits to RM of ICD recipients represents a major change in the delivery of health care although limited information is available that pertains to the organizational aspects of this new means of follow-up. [16][17][18][19] We hypothesized that the development and application of decisional trees to manage telemedical alerts might save medical and paramedical time and lower the variability in the responses of caregivers. We sought to describe our experience with an optimized organization of RM to validate our decisional trees, using a qualitative methodology particularly well adapted to this subject matter.…”
mentioning
confidence: 99%